Figurative Language on Maya Angelou selected Poetries - Hayani, Risma (Script Journal: Journal of Linguistic and English Teaching, 2016)
This study aimed to find out the kinds of figurative language in the five selected poetries of Maya Angelou, the titles are: Alone, Caged Bird, Old Folks Laugh, Phenomenal Woman, Still I Rise. The focus of this study is figurative language which involves: Metaphor, Personification, Hyperbole, Simile, Metonymy, Synecdoche, Irony, Antithesis, Symbolism, and Paradox. Qualitative approach with design of content analysis was used in this study. The researcher acted as the main instrument since she was the one who analyzed the figurative language. Moreover checklist was also used to support her data collection. The data was analyzed through three stages; 1). Data reduction, 2). Data representation, 3). Conclusion. The result of her study showed there were 40 sentences that containing figurative language in five selected poetries of Maya Angelou. They were; Metaphor (13 sentences), Personification (9 sentences), Hyperbole (1 sentence), Simile (8 sentences), Synecdoche (1 sentence), Antithesis (1 sentence), Symbolism (5 sentences), and Paradox (2 sentences). The researcher conclude, if the figurative language used by Angelou to compare, or even symbolize the sentences to bring the meaning come up with beautiful language. Mostly of her poetries told about her experience in the past that rooted to history of the discrimination of American-African.